Service politics and sustainability performance for N27 Constituency, Sarawak / Nur Aida Kipli ... [et al.] - Kipli, Nur Aida; Abdollah, Ida Izumi; Sadikin, Sarehan; Wan Achmed, Sharifah Shaneela (2021)
This is a conceptual paper that would define the constituency's performance achievements in the delivery of service politics in N27 Sebuyau, Kota Samarahan, Sarawak with a population of qualified voters for their constituency. The state constituency led by YB Datuk Hj Julaihi bin Hj Narawi from GPS (Gabungan Parti Sarawak) that formerly known as BN (Barisan Nasional/ National Front) from 1991 until the present. The state constituency of Sebuyau is located at the border of Sri Aman and Simunjan and the population of the area is made up mostly of Malay and Iban people. It is under this pretext that the research is to identify factors that contributed to political sustainability performance. The focus of this paper is to explain the types of contribution and the factors that influence the N27 constituency's longterm success in preserving his position in the constituency through his service politics. The research also assesses the level of voters' judgment on the existing quality of performance served by the administrator apparatus and satisfaction in using public sector services through the policies, decrees, and law.